Reduction of charge-transport characteristics of SiGe dot floating gate memory device with ZrO2 tunneling oxide. - Dong-Won Kim (IEEE Transactions on electron devices)
We have demonstrated the effects of charging voltage and the charge retention characteristics in silicon-germanium dots with ZrO2 tunneling oxide. Using the ZrO2 high-k dielectric tunneling oxide, we achieved a low write voltage and improved retention time as compared to the SiGe dots with a SiO2 tunneling oxide. The discharge behavior of the ZrO2 device is similar to that of Si dots embedded in SiO2 in terms of a logarithmic charge decay. This demonstrates that the SiGe dots with ZrO2 tunneling oxide can be used to replace SiGe dots with SiO2 tunneling oxide as the floating gate in EEPROMs and have a high potential for further scaling of floating-gate memory devices.